One man and three boys beside a pile of logs. They have a sled and are collecting logs for fuel, Fort Chippewyan. Note on the front reads: ""Reverend Roberts and his Sluray sons getting in the winter fuel Fort Chipewyan, 1907"". (1907)
Anglican Church - - Clergy; Anglican Church - - Fort Chippewyan, Alberta; Heating; Wood; Logging